Optical properties of few layered graphene quantum dots. (22nd September 2015) - Choudhary, Raghvendra Pratap; Shukla, Shobha; Vaibhav, Kumar; Pawar, Pranav Bhagwan; Saxena, Sumit
Abstract: Quantum dots provide a unique opportunity to study the confinement effects of electronic wave function on the properties of materials. We have investigated the optical properties of graphene quantum dots synthesized using ultra-fast light–matter interactions followed by one step reduction process. Atomic-scale morphological information suggests the presence of both zigzag and armchair edges in these quantum dots. Optical characterizations were performed using absorption, photoluminescence, and infrared spectroscopy. A shift in the emission spectrum and disappearance of n → π * transition in the absorption spectrum on reduction of the ablated samples confirmed the formation of graphene quantum dots. First principles calculations are in good agreement with the experimentally reported infrared data.